(untitled) (Proceedings of the International Conference on Agriculture, 2025)
Intensive farming negatively affects soil quality, by reducing the soil organic matter and increasing acidification, nitrification, desertification, contamination by agrochemicals, compaction, and erosion. The use of appropriate tillage systems (TS) and fertilizer rates is of importance to reduce these negative impacts on the environment. The integrated effect of TS and compost application on crop performance and soil quality is not often studied and requires more exploration. A factorial experiment was set-up to investigate the interaction effect of compost rate (CR) and TS on soil organic carbon (SOC), teff growth and yield during the 2021-2022 summer cropping season. Treatments consisted of two TS (minimum [MT] and conventional [CT] TS) and three rates of chicken manure co-composted with cattle manure (0, 20 and 40 t ha-1). MT involved chisel-ploughing, whereas CT involved the use of chisel-plough, mould-board plough, and disc-harrow. Grain yield (GY) and SOC from the MT were significantly higher (35% and 69%, respectively) than those recorded from the CT. The 20 t ha-1 rate under MT gave the highest SY (2511 kg ha-1), while the control under CT gave the lowest SY (1223 kg ha-1). Generally, compost application increased SOC, plant height, panicle length, GY and SY by up to 30%, 8%, 15%, 24% and 44% (20 t ha-1), respectively, compared to control. In conclusion, this study revealed that reducing tillage activities leads to more SOC and that it is important to consider the CR and TS interaction when selecting the agronomic practices for optimizing straw production.